Print Grimoires and the Democratization of Learned Magic in the Later Early Modern Period: Bricolage Tradition and the Cross-Cultural Transmission of Knowledge - Davies, Owen (Entangled Religions, 2023)
The relationship between print and manuscript in the entanglement of ‘western learned magic’ provides valuable insights regarding the complexity of cultural transmission across societies and social strata. Through exploring the influence over time of two print books containing conjurations, one in English the other French, we can trace how seemingly tenuous relationships reveal unlikely global frames of reference with regard to learned magic.